Stroje používané pro soustružení - Grulichová, Jana (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2012)
This work deals with lathes, machines used for the turning technology. The aim is to link the general conditions of the turning with the specific products available on the market and specific examples of the use of machines in practice. The first part describes the historical development. The following is description of this technology, including related regularities and the calculation formulas. The third part consists of an overview of lathes including the specific machines, their suitability for the production of different workpieces and their parameters. In the next chapter are examples of the model using of the different lathes direct in the production company, the advantages and disadvantages of their use. The last part is devoted to temporary trends and directions in the development and improvement of these machines and streamlining of the production made with using of them.
Keywords: development; výrobci; soustruhy; historie soustružení; vývoj; producers; turning history; turning machines; popis; description